METHODOLOGICAL FOUNDATIONS OF “SCENARIO-BASED TEACHING” IN DEVELOPING THE PROFESSIONAL SKILLS OF SCRIPTWRITERS (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article discusses the foundations for applying the “Scenario-Based Teaching” methodology in developing the professional skills of scriptwriters, highlighting its effective aspects. Based on the analysis of research conducted on the “Scenario-Based Teaching” method, a set of recommendations has been developed.